Practical implementation of methods for optimization of flow distribution in water supply systems - Добровольська, Оксана Григорівна; Українець, Микола Опанасович (Technology audit and production reserves, 2014)
In this paper it is proposed to use the information on the actual flow rate in the water supply divisions for rapid determination of its hydraulic characteristics. The main aim of the research is to verify the adequacy of the mathematical model of flow distribution in real time, developing of recommendations on the use of information about the actual flow rates in divisions of network to optimize the flow distribution in it. The use of modern telecommunications allows dispatcher to collect and analyze information about the pressures in the network, which comes from sensors in its individual nodes. In the article it is shows that the results of the network calculation of one residential areas of Zaporozhye made taking into account the pressures measured in the control nodes, almost identical to the instrumental measurements. The recommendations on the operational definition of the network hydraulic characteristics allow determining the damaged areas and making decision on the redistribution of flows. The research results can be used in the design, reconstruction of existing water supply systems and to analyze the changes in the resistance of areas in time.